Effects of competition on acute phase proteins and lymphocyte subpopulations – oxidative stress markers in eventing horses. Issue 5 (28th January 2015) - Valle, E.; Zanatta, R.; Odetti, P.; Traverso, N.; Furfaro, A.; Bergero, D.; Badino, P.; Girardi, C.; Miniscalco, B.; Bergagna, S.; Tarantola, M.; Intorre, L.; et al.
Summary: The aim of the study was to evaluate markers of the acute phase response (APR) in eventing horses by measuring acute phase proteins (APP) (haptoglobin, Hp, and serum amyloid A, SAA), lysozyme, protein adducts such as pentosidine‐like adducts (PENT), malondialdehyde adducts (MDA), hydroxynonenal adducts (HNE) and total advanced glycation/glycoxidation end products (AGEs), complete blood count and lymphocyte subpopulations (CD4+, CD8+ and CD21+) both at rest and at the end of an eventing competition. Blood samples were collected from eight Warmblood horses (medium age 10 ± 3) during an official national 2‐day event competition at rest (R) and 10 min after the arrival of the cross‐country test on the second day. Exercise caused a significant increase in red blood cell number, haemoglobin, packed cell volume, neutrophils, white blood cell and lymphocyte number; however, these values remained within the normal range. The CD4+ and CD8+ cells significantly increased, whereas the CD21+ lymphocytes decreased; a significant increase in serum SAA, lysozyme and protein carbonyl derivates was also observed. Two‐day event causes significant changes in APR markers such as lysozyme, protein carbonyl derivates (HNE, AGEs, PENT) and lymphocyte subpopulations. The data support the hypothesis that 2‐day event may alter significantly APR markers. Limitations of the study were the relatively small sample size and sampling time conditioned by the official regulations of the event. Therefore, further studies are needed to investigate the time required for recovery to basal values in order to define the possible effects on the immune function of the athlete horse.